Peran Penelitian Dalam Bidang Pendidikan Sebagai Dasar Pengembangan Kualitas Pembelajaran. - Oktalia, Huda; Hayadi, B.Herawan; Zikriyanto, Wahyu; Nurlena, Elin; Hisaanah, Khauranina; Haryati, Reti Sri (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Research in education plays a crucial role in improving the quality of the learning processes and the development of the education system as a whole. Educational research not only generates new knowledge but also provides a scientific basis for educational decision making related to education policy . This study aims to examine the role of educational research in improving the quality of learning and identify developments in educational research in recent years. The method used in this study is a literature review, analyzing various scientific articles published in the last five years (2020 – 2025). Data was obtained from various national and international journals discussing educational research, learning innovation, and the use of technology in education.. The results of the study indicate that educational research plays a strategic role in identifying learning problems, developing innovative learning models, improving teacher competence, and supporting data driven educational policymaking. Educational research also contributes to curriculum development and the integration of technology into the learning process.